KUALITAS PELAYANAN TERHADAP PENYALURAN BANTUAN DANA KEPADA TUNA DAKSA (KAUM DIFABEL) 2014 (Study Kasus Dinas Sosial Kota Palembang) - Vera Sandika; Rendy Sueztra Canaldhy; Ryllian Chandra (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
Research thesis entitled quality of service to help the disabled (disabled people) in 2014 at the Social Service Palembang. Quality of service to help the disabled (disabled people) in 2014 at the Social Service Palembang background with a lack of public awareness of disabilities. Therefore, seen from this background, the problem can be formulated as follows: How is the quality of services to aid for disabled (disabled people) ?. To explain and describe objectively the author uses descriptive method with data collection techniques such as observation and interviews. While data analysis technique used is qualitative analysis. The results showed that the quality of service to help disabled not meet stndarisasi quality of service, in terms of facilities Social Service not provide a sense of comfort to the community, especially for disabled people because the facilities are not being met such as wheelchairs at the Social Affairs office let alone a special road wheelchair nothing and waiting room chairs are provided only slight, service procedures that are not transparent, employees of governance irreverent speech. Aspects that need to be revisited, namely a review of the facilities and infrastructure that a facility so that people feel comfortable, transparent procedures such as through media or notice boards, governance should talk friendly and courteous, dissemination to the public on the procedure for social assistance services. Keywords : Quality of Service, Disabled